From policy design to campus: Implementation of a tuition decentralization policy. - Harris, Michael S. (Education Policy Analysis Archives, 2007)
This study analyzes the implementation of a tuition decentralization policy in North Carolina. Concepts of organizational culture served as a guiding framework for an interpretive analysis. Qualitative case study data for the research was collected from interviews with key policy makers within the University of North Carolina as well as an extensive collection of documents. The findings demonstrate the importance of shared norms and beliefs in achieving successful policy implementation through a case study where incongruence of stakeholder values, beliefs, and goals created institutional conflict.